Avaliação das propriedades de armazenagem de hidrogênio através de reação sólido-gás e eletroquímica da liga multicomponente (TiNb)(CrMnFe)₂ com estrutura de Fase Laves tipo C14 - Aranda, Vinícius (2023)
Hydrogen is critical for storage and transport of renewable energy. Because it is low-density gas, one of the biggest challenges of its widespread use as an energy vector is in its hardly storage. Metal hydrides are strategic materials for the implementation of hydrogen-based energy in our society, since they can both be used in solid-state storage tanks, enhancing the volumetric energy density of hydrogen, and in Ni-metal hydrides type batteries. The hydrogen storage properties of metals are strongly dependent on their chemical composition, and for this reason, high entropy alloys or multi-component alloys capable to form metal hydrides have attracted attention. The wide compositional field of multi-component alloys allows engineers and materials scientists to design alloys with optimized properties to each specific application. In this regard, the aim of this master’s project was to produce, characterize and evaluate the hydrogen storage properties of the (TiNb)(CrMnFe)2 alloy, derived from the TiZrCrMnFeNi alloy reported previously in the literature and with promising properties. The (TiNb)(CrMnFe)2 arc-melted alloy showed a single-phase Laves phase structure pf C14-type. The hydrogen storage properties were assessed in the solid-gas and electrochemical reaction in alkaline aqueous solution, which occur in batteries, and compared with those of the TiZrCrMnFeNi alloy. The (TiNb)(CrMnFe)2 shows a high equilibrium pressure at room temperature with a capacity of 0.18 H/M at 80 bars. These results were discussed based on a thermodynamic model for predicting the pressure-composition-temperature diagrams of alloys with Laves phase structure of C14-type. The alkaline electrochemistry behavior of both alloys was quite similar. The equilibrium hydrogen absorption pressure of the (TiNb)(CrMnFe)2 alloy is much higher than that of the TiZrCrMnFeNi, and since these pressures are above 1 bar, electrochemical hydrogenation indicates low absorption capacity for both.